2022
DOI: 10.1590/fst.26522
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of neryl acetate by free lipase-catalyzed transesterification in organic solvents and its kinetics

Abstract: In this paper, the optimum conditions and kinetics of lipase-catalyzed transesterification reaction of nerol and vinyl acetate for the synthesis of neryl acetate were investigated in a solvent-free system. The optimum conditions were determined as follows: the reaction temperature was 40 °C, the amount of enzyme was 12 mg/mL, and there was no need to add water. Increasing the stirring speed to 200 r/min can eliminate the external diffusion limitations. There was no substrate inhibition when the substrate conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…After the above optimization, the yield of neryl acetate could reach over 99% after 3 h of reaction. This was a significant improvement on our previous study [27], and although the final yield of neryl acetate was almost the same, the reaction time was greatly reduced. In contrast to other literature, Zong et al [47] successfully produced neryl acetate by biosynthesis using recombinant Escherichia coli.…”
Section: Effect Of Rotating Speedmentioning
confidence: 52%
See 3 more Smart Citations
“…After the above optimization, the yield of neryl acetate could reach over 99% after 3 h of reaction. This was a significant improvement on our previous study [27], and although the final yield of neryl acetate was almost the same, the reaction time was greatly reduced. In contrast to other literature, Zong et al [47] successfully produced neryl acetate by biosynthesis using recombinant Escherichia coli.…”
Section: Effect Of Rotating Speedmentioning
confidence: 52%
“…The results indicated that the optimal reaction temperature for the immobilized enzyme to catalyze the reaction was 50 °C. Compared to the optimal reaction temperature of 40 °C for the free enzyme [ 27 ], it increased by 10 °C. This also indicated that the thermal stability of the immobilized enzyme was greatly improved compared to that of the free enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction kinetic is very important both for understanding the fundamental reaction mechanism and for practical production (Sun et al, 2022;Xiong et al, 2022). Isomerization of sesamin to asarinin is a reversible reaction as schemed in Figure 1.…”
Section: Kinetic Studiesmentioning
confidence: 99%